Positive Participatory Organizational Interventions: A Multilevel Approach for Creating Healthy Workplaces - Nielsen, Karina; Christensen, Marit (Frontiers in Psychology, 2021)
In the following perspective paper, we argue for the importance of conducting research on positive participatory organizational interventions. We propose that these types of interventions are important because they not only focus on eliminating or reducing adverse job demands but focus also on developing job resources. To achieve the best effects, actions should be taken to address demands and resources at the individual, group, leader and organizational levels. We furthermore suggest that the participatory intervention process itself may also build resources at these four levels.